(untitled) (The Pakistan Development Review, 2003)
The study of men in involvement and use of family planning methods is important because of their dominant role in family decision-making in the socio-structural context of Pakistan. The objective of present study is to examine the changes in knowledge and attitude of men about family planning, and also to estimate the extent to which it affects their contraceptive use behaviour. The findings show that men’s knowledge and contraceptive use has increased three times during the period from 1968-69 to 1990. The important factors that determine men’s contraceptive use behaviour are the approval of family planning, the communication with wife on family planning matters, and the desire for children. The multivariate analysis shows that men living in urban areas, with greater knowledge and a positive attitude towards family planning, are more likely to use contraception. In addition, wife’s autonomy is also important in explaining men’s involvement in the use of family planning. The study reveals that most Pakistani men approve of family planning and suggests that men should receive an equal focus together with women in the population welfare programme activities.